2022
DOI: 10.1111/ijmr.12312
|View full text |Cite
|
Sign up to set email alerts
|

The relevance and impact of business schools: In search of a holistic view

Abstract: The degree to which business schools are relevant and impactful for society has been disputed. Critics that engage in the so-called 'relevance problem' have argued that business schools are preoccupied with academic rigour at the expense of practical relevance, resulting in a lack of societal impact. This systematic literature review synthesizes the fragmented body of knowledge pertaining to the relevance and impact of business schools. Appreciating the contributions of both research and education, this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 130 publications
0
0
0
Order By: Relevance
“…For our integrative review, we included journals across 12 domains (i.e., Entrepreneurship and Small Business Management, General Management, Ethics, and Social Responsibility, Human Resource Management, and Employment Studies, Innovation, International Business and Area Studies, Management Development and Education, Organization Studies, Psychology [Organizational], Regional Studies, Planning and Environment, Sector Studies, Operation Management, Strategy ). Several recent integrative review studies have used the same selection procedure, for example, Gamble & Muñoz’s (2022) examination of value detraction among non-profit organizations, Redgrave et al’s (2022) review of the relevance and impact of business schools, and Thomas and Tee’s (2022) integrative conceptual framework on generativity. The categories included in the ABS AJG list cover most of the research spectrum conducted by scholars involved in schools of business, management, or economics (Gamble & Muñoz, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For our integrative review, we included journals across 12 domains (i.e., Entrepreneurship and Small Business Management, General Management, Ethics, and Social Responsibility, Human Resource Management, and Employment Studies, Innovation, International Business and Area Studies, Management Development and Education, Organization Studies, Psychology [Organizational], Regional Studies, Planning and Environment, Sector Studies, Operation Management, Strategy ). Several recent integrative review studies have used the same selection procedure, for example, Gamble & Muñoz’s (2022) examination of value detraction among non-profit organizations, Redgrave et al’s (2022) review of the relevance and impact of business schools, and Thomas and Tee’s (2022) integrative conceptual framework on generativity. The categories included in the ABS AJG list cover most of the research spectrum conducted by scholars involved in schools of business, management, or economics (Gamble & Muñoz, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Kociatkiewicz et al [28] comment that the curriculum of the business school is seen as upholding capitalist relationships. However, business schools are often absorbed in academic rigour, potentially neglecting practical relevance and, consequently, diminishing societal impact [44].…”
Section: The Characteristics Of Business Schoolmentioning
confidence: 99%
“…There is significance in business schools emphasizing practical wisdom alongside providing scientific and technical expertise. Management education encompasses the development of applied sagacity, surpassing the mere dissemination of factual scientific information, proficiencies, and methodologies [44,49]. It has been suggested that a significant portion of the research conducted in business schools focuses excessively on scientific rigour while overlooking practical applicability, commonly referred to as the gap between rigour and relevance [44].…”
Section: The Characteristics Of Business Schoolmentioning
confidence: 99%
“…However, these methods often lack a comprehensive, learner-centric approach to higher education. Despite the 1 Professor of Marketing, University of Lyon 2, France integration of various methodologies, research indicates that business colleges often neglect the holistic aspect of higher education (Redgrave, Grinevich, and Chao 2022). This neglect results in insufficient emotional, spiritual, and social development in learners, limited interdisciplinary learning opportunities, and inadequate emphasis on human relationships within the current educational paradigm.…”
Section: Introductionmentioning
confidence: 99%